2007
DOI: 10.1152/ajpregu.00085.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of ventrolateral medulla in generating the 10-Hz rhythm in sympathetic nerve discharge

Abstract: We recorded changes in right inferior cardiac and either left inferior cardiac or left vertebral sympathetic nerve discharge (SND) produced by unilateral microinjections of GABA-A and excitatory amino acid (EAA) receptor antagonists into the ventrolateral medulla (VLM) of urethane-anesthetized, baroreceptor-denervated cats. Unilateral microinjections of GABA-A receptor antagonists, SR-95531 or bicuculline, into single tracks in VLM anywhere between 1 and 5 mm rostral to the obex eliminated or markedly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…With this approach, one can quantify the average duration of integrated epoch or the slope of the integrated signal. In this example, the amount of SNA markedly decreased as sequential injections of a GABA-A receptor antagonist (upward tick marks in the trace below SNA) were made into the caudal ventrolateral medulla (CVLM) of a urethane-anesthetized cat (Barman and Gebber, 2007). …”
Section: Quantifying the Level And Pattern Of Snamentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach, one can quantify the average duration of integrated epoch or the slope of the integrated signal. In this example, the amount of SNA markedly decreased as sequential injections of a GABA-A receptor antagonist (upward tick marks in the trace below SNA) were made into the caudal ventrolateral medulla (CVLM) of a urethane-anesthetized cat (Barman and Gebber, 2007). …”
Section: Quantifying the Level And Pattern Of Snamentioning
confidence: 99%
“…Although most recognized for having cardiac-related and respiratory-related discharges, sympathetic neural networks are quite complex and generate a variety of periodicities that range between ~0.04 and 10 Hz or even higher, and even diurnal variations, depending on the physiological or pathophysiological conditions, type of nerve being analyzed, age of the subject, and the species (Barman and Gebber, 2000; Barman and Kenney, 2007; Chang et al, 1999; Charkoudian and Wallin, 2014; Hashimoto et al, 1999; Malpas, 1998, 2010; Narkiewicz et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Potentials were recorded monophasically from the central ends of the cut nerves placed on platinum bipolar electrodes. The capacitycoupled preamplifier band pass was set at 1-1,000 Hz so that the synchronized discharges of sympathetic fibers appeared as slow waves (4,5,7,24).…”
Section: Methodsmentioning
confidence: 99%
“…Third, chemical inactivation of the rostral VLM, caudal VLM, or medullary raphé with microinjection of muscimol reduces or eliminates 10-Hz SND (10,39). Barman and Gebber (7) reported that unilateral microinjections of as little as 6.25 pmol of the selective GABA-A receptor antagonist SR-95531 into the VLM at any level between 1 and 5 mm rostral to the obex eliminated 10-Hz SND. This led Barman and Gebber (7) to propose that 1) GABAergic transmission in the VLM is critical for generation of the 10-Hz rhythm, and 2) neurons in caudal and rostral portions of the VLM act in combination to help generate the 10-Hz rhythm in SND.…”
mentioning
confidence: 99%
“…In both human and animal studies, increases in RVLM activity are known to be associated with SNA and SNA-related changes in BP [39][40][41][42][43]. The RVLM expresses both ERα and ERβ receptors [44], and activation of these receptors via direct injection of oestrogen into the RVLM results in a decrease in SNA [45].…”
Section: The Rostral Ventral Lateral Medullamentioning
confidence: 99%